Analisis Pelaksanaan Akad Murabahah dalam Pembiayaan Pembelian Rumah (PPR) Syariah, Studi Kasus Bank Syariah Indonesia KCP Medan Marelan - Risky Sobari; Tuti Anggraini; Nurul Inayah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Finding out how Bank Syariah Indonesia KCP Medan Marelan implements murabahah contracts is the aim of this study and to evaluate the DSN MUI Fatwa Number 04/DSN-MUI/IV/2000 for the appropriateness of implementing this sharia KPR. The study employs a qualitative descriptive methodology, collecting data from primary and secondary sources such as interviews and literature reviews encompassing books, statutes, papers, and so on. According to the research findings, the DSN MUI fatwa Number 04/DSN-MUI/IV/2000 is followed when implementing a murabahah contract to finance the purchase of a sharia house or sharia house ownership (KPRS), in terms of financing stages or procedures, the amount of funds provided, financing without usury, and other factors